T-cell rich B-cell lymphoma of the breast: A rare case report with emphasis on the role of immunohistochemistry in the diagnosis (Indian Journal of Case Reports, 2018)
Primary breast lymphoma is one of the rare tumors that commonly presents as a lump with <0.5% incidence rate. It may be misdiagnosed as poorly differentiated carcinoma on routine fine-needle aspiration cytology. With appropriate treatment, this breast malignancy has a relatively better prognosis. Here, we report the case of a mammary T-cell rich B-cell non-Hodgkin lymphoma in a pre-menopausal woman diagnosed by biopsy and later confirmed by immunohistochemistry.